Access to Production Information Citrus Atisbo Local Government Area of Oyo State. - P O Eniola; O P Fawole (Journal of Agricultural Extension, 2007)
This study was conducted to determine the level of awareness, access andutilization to sixteen, citrus production information by citrus farmers in ATISBO Local Government Area of Oyo State. Structured interview scheduled were administered on sixty citrus farmers who werepurposivelyselectedfrom six communities. Descriptive statistics such as frequency distribution, percentages andrating were used to analyse the data. Ninetyeight point three percent (98.3%) of the respondents were male and 85 percent were married. The main source of information were village extension agents and contact farmers as indicated by 46.7 percent and 41.6 percent of respondents. Sixty eight percent of the farmers experiencedlow yield citrus. Level of information awareness, accessandutilization on citrus farmpractices waslow. Thatis 63.3, 56.66and50percent of the respondents had low scores respectively. The extension agents have been encouraged to release to farmers necessary information that could lead to high citrus production in the area.